Reducing Generalization Error Using Autoencoders for The Detection of Computer Worms - Nelson Ochieng Odunga; Ronald Waweru Mwangi; Ismail Ateya Lukandu (Universitas Sriwijaya, 2020)
This paper discusses computer worm detection using machine learning. More specifically, the generalization capability of autoencoders is investigated and improved using regularization and deep autoencoders. Models are constructed first without autoencoders and thereafter with autoencoders. The models with autoencoders are further improved using regularization and deep autoencoders. Results show an improved in the capability of models to generalize well to new examples.